A Catalog of Quasar Candidates Identified by Astrometric and Mid-infrared Methods in Gaia EDR3. (1st February 2023) - Wu, Qiqi; Liao, Shilong; Qi, Zhaoxiang; Luo, Hao; Tang, Zhenghong; Cao, Zihuang
Abstract: Quasars are very important in materializing the reference frame. The excess emission of active galactic nuclei (AGNs) in the mid-infrared band can be used to identify quasar candidates. As extremely distant and point-like objects, quasars also could be further selected by an astrometry method. Increasing the number of reliable quasar candidates is necessary in characterizing the properties of Gaia astrometric solution and evaluating the reliability of Gaia's own quasars classification. We identify quasars by using appropriate AllWISE [W1-W2] color and different combinations of astrometric criteria. Together with the contamination and completeness, the magnitude, astrometric properties, density distribution, and the morphological indexes of these selected quasars are evaluated. We obtain a quasar candidate catalog of 1, 503, 373 sources, which contains 1, 186, 690 candidates (78.9%) in common with the Gaia EDR3_AGN catalog and 316, 683 newly identified quasar candidates. The completeness of this catalog is around 80% compared to LQAC5, and the purity of the overall catalog is about 90%. We also found that the purity of quasar candidates selected by this method will decrease in the crowded sky area and the region with less WISE observations.